́Ich wäre gerne ein Engel ́. Zu Peter Roos' Demaskerade seines als Kunstwerk verkleideten Geschlechtskörpers - Öhlschläger, Claudia; Bettinger, Elfi (Maskeraden. Geschlechterdifferenz in der literarischen Inszenierung)

Rezension zu Susanne Lummerding: "Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes. Wien: Passagen 1994 - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 44: Zensur. Mai 1995)

Conformance Tests of Very Large STEP Files - Lehrenfeld, Georg; Müller, Wolfgang; Wiechers, N. (Proceedings of the 4th EXPRESS User's Group)

Pen-based Interfaces for Engineering Environments - Zhao, R.; Kaufmann, H. J.; Kern, T.; Müller, Wolfgang

Transforming SDL Diagrams Into a Complete Visual Representation - Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of Symposium on Visual Languages)
We investigate a translation of SDL diagrams into the complete visual representation of Pictorial Janus (PJ) programs in order to analyze the specification by visual debugging and animation. We additionally introduce timing concepts to PJ (Timed PJ) for a mapping of the SDL timing statements. The concepts transforming SDL interaction and process diagrams into Timed PJ are outlined by an example sketching the transformation of an Ethernet CSMA/CD protocol specification.
Keywords: Animation; Timing; Debugging; Ethernet networks; Multiaccess communication; Protocols; Computer languages; Prototypes; Environmental management; Visualization

Validation of EXPRESS Models - Müller, Wolfgang; Lehrenfeld, Georg; Wiechers, N.

SINGLE-STAGE AND DOUBLE-STAGE ACOUSTOOPTICAL TI-LINBO3 TE-TM CONVERTERS USED IN WAVELENGTH-SELECTIVE POLARIMETER AND POLARIZATION-INDEPENDENT DEPOLARIZER - REHAGE, M; Noé, Reinhold; HARIZI, C; RICKEN, R (FIBER OPTIC NETWORK COMPONENTS)

Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft)

Guide to EXPRESS-P - Müller, Wolfgang; Felser, W.; Buijs, F. (Proceedings of the 4th EXPRESS User's Group)
Greenville, South Carolina

Complete Visual Specification and Animations of Protocols - Müller, Wolfgang; Lehrenfeld, Georg; Tahedl, C. (Proceedings of ASP-DAC'95/CHDL'95/VLSI'95 with EDA Technofair)
This article discusses the application of Pictorial Janus (PJ) for the rapid development and analysis of protocols by animation and complete visualization. In order to make PJ applicable in the context of hardware description we first extend PJ by timing facilities (Timed PJ) and introduce an approach for integrating VHDL models into this visual framework preserving the simulation semantics of VHDL. We finally give the example of the specification and animation of a non interlocked protocol.
Keywords: Animation; Protocols; Timing; Computer languages; Electronic mail; Context modeling; Visualization; Control systems; Flow graphs; Trademarks

An Editor for the Rapid Prototyping of EXPRESS-G Models - Zhao, R.; Müller, Wolfgang; Kaufmann, H. J.; Kern, Th.; Buijs, F. (Proceedings of the 5th EXPRESS User's Group)

The Process Modeling Language EXPRESS-P - Müller, Wolfgang; Felser, W.; Wiechers, N.

Trigonometric convolution structures on Z derived from Jacobi polynomials - Rösler, Margit (Journal of Computational and Applied Mathematics)
Keywords: Applied Mathematics; Computational Mathematics

Quantum beats from biexcitons in narrow quantum wells: polarization and density dependence - Meier, Torsten; Albrecht, T.F.; Schulze, A.; Koch, M.; Bott, K.; Feldmann, J.; Stolz, W.; Kuhl, J.; Mayer, E.J.; Koch, S.W.; Göbel, E.O.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Transient four-wave mixing (TFWM) has been extensively used during the last few years to study exciton dynamics in semiconductors and in semiconductor heterostructures. These studies have provided significant insight into exciton dynamics in both ordered and disordered systems. There are, nevertheless, still certain aspects of the excitonic TFWM response that are not completely understood. In particular, a complete understanding of the polarization and intensity dependences of the signai strength, the decay of the time-integrated signal, and the temporal characteristics of the time-resolved signal has proven elusive. Recent theoretical and experimental work has indicated that exciton-exciton interactions are important.1·2 Such interactions include incoherent processes, such as excitation-induced dephasing, and the formation of biexcitons. Additionally, some of the phenomena result from disorder, making them sample dependent.

Polarization dependence of quantum beats between light-hole and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Heuckeroth, V.; Thomas, P.; Koch, M.; Hey, R.; Ploog, K. (Quantum Electronics and Laser Science Conference)
The appearance of quantum beats (QBs) between heavy-hole (hh) and light-hole (lh) excitons in GaAs quantum wells (QWs) has been observed in many degenerate-four- wave-mixing (DFWM) experiments with subpicosecond optical pulses. Although the variation of the beat amplitude and phase with polarization of the incident pulses was recognized early on, a consistent theoretical interpretation of exciton coherence for the case of simultaneous excitation of hh and lh excitons is still missing.

Paralleles Sortieren auf mehrdimensionalen Gittern - Wanka, Rolf

Weak Sequential Composition in Process Algebras - Rensink, Arend; Wehrheim, Heike (CONCUR '94, Concurrency Theory, 5th International Conference, Uppsala, Sweden, August 22-25, 1994, Proceedings)

Parametric Action Refinement - Wehrheim, Heike (Programming Concepts, Methods and Calculi, Proceedings of the IFIP {TC2/WG2.1/WG2.2/WG2.3} Working Conference on Programming Concepts, Methods and Calculi {(PROCOMET} '94) San Miniato, Italy, 6-10 June, 1994)

Der deutsche Roman 1815-1830. Bibliographie. Standortverzeichnisse, Rezensionen, Forschungsüberblick - Eke, Norbert Otto; Olasz-Eke, Dagmar

Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit

Heiner Müller - Eke, Norbert Otto (Deutsche Dichter des 20. Jahrhunderts)

„Lieber Niembsch“ oder: Der Dichter im Gehäus. Anmerkungen zu Manfred Karges Spiel mit Biographie und Geschichte um den Autor im „Stadium der Verrücktheit“ - Eke, Norbert Otto (Lenau-Forum)

Vergangene Zeiten. Anmerkungen zur Semantik des Umbruchs und zu den Bedeutungsstrukturen im historischen Erzählen der frühen Restaurationszeit (1815-1830) - Eke, Norbert Otto (Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit)

Der historische Roman der frühen Restaurationszeit. Zur Einführung - Eke, Norbert Otto; Steinecke, Hartmut (Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit)

Fundamentals of Object-Oriented Languages, Systems, and Methods
During the last decades there has been progress within the object-oriented community in agreeing on what object- orientedness means. The role of object identity, specialization, inheritance, and dynamic binding have been examined. However, a careful look at articles written by people with a theory, programming language, database, and software engineering background shows that the semantical understanding of the same features still differs considerably. A well-known example is the feature of inheritance, which has quite a different meaning for persons from the database comunity with a semantic data model background and persons form the programming language community with a compiling technique background This observation also applies to the literaute on object-oriented software development methods. Here, object -oriented analysis and design methods are often heavily influenced by semantic data modelling consepts- An implemantion of an object-orinted design by an objeckt-oriented progamming language usually causes more difficulties than expected although the "same" object-oriente paradigm is used...

Graph Gramars and Their Application to Computer Science, 5th International Workshop (1994), Selected Papers

Berücksichtigung von Datenschutzaspekten in einem bevölkerungsbezogenen Krebsregister - Thoben, Wilfried; Appelrath, Hans-Jürgen; Rettig, Jens; Sauer, Stefan (Proceedings of the conference on Medizin und Information, Biometrie und Epidemiologie (GMDS 1994), Dresden (Germany))
Die Pilotphase 1993/ 94 zum Aufbau eines Niedersächsischen Krebsregister untersucht das im Entwurf des Bundeskrebsregistergesetzes vorgesehen Modell für ein bevölkerungsbezogenes Krebsregister. Darin werden die Krebsmeldungen in einer Vertrauensstelle erfaßt und die personenidentifizierenden Daten vor der Übermittlung an die Registerstelle anonymisiert, wo sie dann zu einem bevölkerungsbezogenen Krebsregister verdichtet und epidemiologischer Forschung zur Verfügung gestellt werden ([1], [2], [3]). Dieses sogenannte „Michaelis“-Modell erlaubt eine bevölkerungsbezogene Registrierung von Krebsfällen unter Berücksichtigung datenschutzrechtlicher Aspekte („Informationelles Selbstbestimmungsrecht“) der einzelnen Betroffenen. In vier Teilprojekten werden dabei in der Modellregion Weser-Ems die Integration krebsregistrierender Einrichtungen, die Chiffrierung/ Dechiffrierung von Krebsmeldungen, der Abgleich anonymisierter Meldungen in der Registerstelle und die Entwicklung eines epidemiologischen Informationssystem betrachtet ([4], [5]).

Structural and Behavioural Views on OMT-Classes - Ebert, Jürgen; Engels, Gregor (Proceedings of the International Symposium on Object-Oriented Methodologies and Systems (ISOOMS 1994), Palermo (Italy))
Object-oriented specification languages provide means to specify the static structure, as well as the allowed dynamic behaviour of objects. Here, the dynamic behaviour is usually described by giving the methods and a state transition diagram which defines the allowed sequences of methods on objects of a certain class. Specialized classes are defined using the inheritance relationship. In order to enable reusability while guaranteeing type substitutability, subclass specifications have to be compatible with respect to static and dynamic aspects with their corresponding superclass specifications. Classes have to provide a large shopping list of operations to satisfy the needs of all possible users. The interests of specific users are often restricted to a subset of operations and thus to a restricted behaviour. This paper describes a formalization of class descriptions given by attributes, operations, as well as state transition diagrams. It defines compatibility between sub- and superclasses and introduces the notion of views in the sense of hiding parts of a class description. It turns out that a view has the same properties as a (virtual) superclass.

Object-Oriented System Development: Will the New Approach Solve Old Problems? - Engels, Gregor; Kappel, Gerti (Proceedings of the IFIP 13th World Computer Congress on Information Processing, Hamburg (Germany))
Object-oriented system development is wideley recognized as improving productivity and reducing system maintenance costs. However, existing approaches have not sufficiently addressed the following three questions which are equally important to users and researchers. Firstly, what are the benefits of object-oriented system development compared to traditional approaches? Secondly, what are the essential features of an objectoriented life cycle model to fulfill the benefits of object-oriented development? And thirdly, what are the pitfalls of object-oriented development and how to cope with them? The paper investigates answers to all three questions in concert.

Towards a Module Concept for Graph Transformation Systems: The Software Engineering Perspective - Engels, Gregor; Ehrig, Hartmut (Proceedings Colloquium on Graph Transformation and its Application in Computer Science)

Actual Optical and Thermal Performance of PV-Modules - Krauter, Stefan (Proceedings of the 1st World Conference on Photovoltaic Energy Conversion (Joint Congress of IEEE/PVSEC/EUPVSEC), Waikoloa, Hawaii (USA), 5.–9. Dezember 1994, S. 734–737.)

Observable or Invocable Behaviour - You Have to Choose - Ebert, Jürgen; Engels, Gregor

Syntax and Semantics of Hybrid Database Languages - Andries, Marc; Engels, Gregor (Proceedings of the International Workshop on Graph Transformations in Computer Science (1993), Dagstuhl (Germany))
We present the hybrid query language HQL/EER for an Extended Entity-Relationship model. As its main characteristic, this language allows a user to freely mix graphical and textual formulation of a query. We show how syntax and semantics of this hybrid language are formally defined by means of a slightly extended version of PROGRES, a specification formalism based on programmed and attributed graph rewriting systems.

Specification of coordinated behaviour by SOCCA - Engels, Gregor; Groenewegen, Luuk (Proceedings of the Third European Workshop on Software Process Technology (EWSPT 1994), Villard de Lans (France))

Visual Specification of Complex Database Actions - Engels, Gregor; Löhr, Perdita (Proceedings of the 2nd International East/West Database Workshop, Klagenfurt (Germany))
The paper presents an approach to specify in an integrated way by visual, diagrammatic languages the structural and behavioural aspects of database applications. Hereby, well-known extended Entity-Relationship diagrams are employed to specify the structural aspects. The behavioural aspects of a database application are specified by using ViAL (Visual Action Language). ViAL specifications are a special kind of data (or better object) flow diagrams, where so-called elementary actions are used as basic building blocks. These elementary actions are automatically derived from a given EER diagram. They guarantee that after finishing their execution all inherent integrity constraints are fulfilled. The paper explains the features of the language ViAL and gives some illustrating examples.

Visuelles Spezifizieren von komplexen Aktionen auf Datenbankstrukturen - Löhr-Richter, Perdita; Engels, Gregor (GI-Datenbank Rundbrief)

Design Representation - Ebert, Jürgen; Engels, Gregor (Encyclopedia of Software Engineering)
This article gives an overview on how to represent the outcome of the software design phase in design documents. The descriptive aspects of the design description languages are stressed. The focus is on sequential systems and the description is arranged according to the main paradigms that are used in indentifying software components. Following a general discussion on how to represent software architectures of large systems, each design paradigm is discussend separately with its basic concepts, its historical background and its main variants. Some multiparadigmatic approaches are discussed, as well which integrate several of the aspects introduced before.

SOCCA: Specifications of Coordinated and Cooperative Activities - Engels, Gregor; Groenewegen, Luuk (Software Process Modelling and Technology)

Dynamic Perfect Hashing: Upper and Lower Bounds - Dietzfelbinger, Martin; Karlin, Anna; Mehlhorn, Kurt; Meyer auf der Heide, Friedhelm; Rohnert, Hans; Tarjan, Robert E. (SIAM Journal on Computing)

Visualization education - Domik, Gitta (Comput. Graph.)

User Modeling for Adaptive Visualization Systems - Domik, Gitta; Gutkauf, Bernd (Proceedings IEEE Visualization '94, Washington, DC, USA, October 17-21, 1994)

Approximate solution of a linear programming problem using a modified perceptron-algorithm. - Hüllermeier, Eyke (in Proceedings EUFIT-94 2nd European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Experimental Evaluation of Multi-DSP Architectures in High Performance Applications - Platzner, Marco; Steger, Christian; Weiss, Reinhold (Proceedings of the 7th Mediterranean Electrotechnical Conference)

Energetics and Structure of Ordered Sb Overlayers and Sb Clusters on GaAs(110) Probed by Ab Initio Calculations - Bechstedt, F; Schmidt, Wolf Gero; Wenzien, B (Europhysics Letters (EPL))

First principles calculations of interface phonons of an Epitaxial Sb monolayer on GaAs(110) and InP(110) - Schmidt, Wolf Gero; Srivastava, GP (Solid State Communications)

Erik Heijerman/H. Walter Schmitz (eds.), Significs, Mathematics and Semiotics. The Signific Movement in the Netherlands. Proceedings of the International Conference Bonn 19–21 November 1986. Nodus Publicationen: Münster 1991 (= Materialien zur Geschichte der Sprachwissenschaft und der Semiotik; 5) - Peckhaus, Volker (Modern Logic)

Alexander Rüstow's Thesis, Beitrag für russell-l@mcmail.cis.mcmaster am 17. Juni 1994 [Abdruck: Rüstow’s Thesis on Russell’s Paradox, History of Logic Newsletter, Nr. 13 (September–Oktober 1994), 2–3] [revidierte Fassung: Rüstow’s Thesis on Russell’s Paradox”, Modern Logic 5 (1995), 167–169] - Peckhaus, Volker
[Abdruck siehe 7.13, revidierte Fassung 4.18]

[Art.] Kunstsoziologie - Süßmann, Johannes (Spezielle Soziologien. Problemfelder, Forschungsbereiche, Anwendungsorientierungen)

Michael Hamburgers Übersetzungen und einige neue Tendenzen in der englisch-sprachigen Hölderlin-Rezeption - van Laak, Lothar; Bartels, Kathrin; Brenig, Claudia; Prudlo, Marion (Hölderlin-Jahrbuch 29)

"In den Wald gehen, tief in den Wald hinein" Autoerotische Phantasmen männlicher Autorschaft in Thomas Bernhards Holzfällen. Eine Erregung - Öhlschläger, Claudia (AUTO(R)EROTIK. Gegenstandslose Liebe als literarisches Projekt)

Maskerade. Bericht über das 3. Symposium des Münchener Graduiertenkollegs Geschlechterdifferenz & Literatur. Ludwig- Maximilians-Universität München (27.-29.10.1994) - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 43: Postfeminismus. Dez. 1994)

"Weibsfauna". Zur Koinzidenz von Tiergeschichte und Pornographie am Beispiel von Bambi und Josefine Mutzenbacher - Öhlschläger, Claudia; Schmidt, Dietmar (Hofmannsthal-Jahrbuch 2)

Sprachbiographie und Sprachstörung. Fallstudien zur Textproduktion bei hirnorganischen Erkrankungen

EXPRESS-P - Eine Erweiterung von ISO 10303-11 zur Prozessmodellierung - Felser, W.; Müller, Wolfgang

FADE: A Layout Facility for Graph-Based Diagrams - Eikerling, Josef; Müller, Wolfgang (Proceedings of the 17th Annual Computer Science Conference)
In this paper we present a novel approach to the layout problem of dimensional graph based dia grams We introduce a framework for e ciently solving constrained layout problems encompassing geometrical and graph based algorithms especially dedicated to the generation of diagrams These concepts as well as the aesthetics for the read ability of diagrams are presented by introducing FADE FADE is a user parametrizable frame work for the generation of EXPRESS G diagrams Our present implementation is discussed consider ing extensions to other classes of graphs and layout problems Additionally competitive approaches in this domain and their limitations are critically reviewed.

Implementing Simultaneous Design: A Case Study - Hyhuis, D.; Müller, Wolfgang (Proceedings of the 2nd International Conference on Concurrent Engineering & Electronic Design Automation (CEEDA94))

Implementierung eines parallelen Validierungswerkzeugs für STEP-Produktdaten unter PVM - Müller, Wolfgang; Lehrenfeld, Georg; Wiechers, N.

The Semantics of Behavioral VHDL'93 Descriptions - Börger, Egon; Glässer, Uwe; Müller, Wolfgang (Proceedings of EURO-DAC'94/EURO-VHDL'94)

Ein paralleles Framework fuer die Validierung von STEP-Produktdaten - Lehrenfeld, Georg; Müller, Wolfgang; Wiechers, N.

Parallel Validation of STEP Files - Lehrenfeld, Georg; Müller, Wolfgang; Wiechers, N. (Proceedings of the 2nd International Conference on Concurrent Engineering & Electronic Design Automation (CEEDA94))

Computational Model of a Logical Visual Programming Language - Lehrenfeld, Georg; Müller, Wolfgang

EXPRESS-P - Extending EXPRESS for Process Modeling and Monitoring - Felser, Winfried; Müller, Wolfgang (Proceedings of the 1994 ASME Computers in Engineering Conference)
The upcoming ISO standard EXPRESS has been de- #ned as a data speci#cation language for the use within STEP. EXPRESS supports the modeling of static structural relationships and consistency constraints whereas the applicability of EXPRESS for the modeling of behavior is very limited. Thus, at present there is an ongoing discussion by which means EXPRESS should be extended with.

Contributions of Bound and Unbound Two-Exciton States to the Nonlinear Optical Response of GaAs Quantum Wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
The strong influence of exciton/exciton interaction on the nonlinear optical response of the 2D exciton in GaAs quantum wells has been demonstrated in several recent experimental studies. The theoretical model for the microscopic coupling mechanism is still the subject of controversy, however. In ref. [1], we have presented a model including a density dependent coupling between opposite spin excitons which assumes that the interaction results in a renormalization of the matrix elements, dephasing rates and energies of the transition from the single-exciton state to the two-exciton state with respect to the corresponding quantities for the single exciton transitions. In contrast, Wang et al. claim that all experimental observations are explained by a density induced dephasing rate and that biexciton states play no role [2]. Here we present a new 3-pulse degenerate-four-wave-mixing (DFWM) configuration which is able to differentiate between pure local field effects and biexcitonic contributions to the time-integrated signal. Experiments were performed on an almost homogeneously broadened GaAs/Al0.3Ga0.7As single QW (well width 20 nm, photoluminescence line 0.3 meV, homogenous linewidth 0.15 meV) in the backward reflection geometry. The sample was cooled to 10 K and excited by a sequence of three pulses (1.1 ps duration) with equal intensity, wave vectors 𝑘→1,𝑘→2,𝑘→3 and delays τ12 and τ13 between the second and first and the third and first pulse, respectively. The signal was monitored in the direction 𝑘→𝑠=𝑘→1+𝑘→2−𝑘→3 which provides no signal for the chosen pulse length if local field and renormalization effects are negligible. The peak intensity of the time-integrated DFWM signal has been calculated by solving the optical Bloch for a system of two non-interacting two-level systems (2LS) with opposite circular polarization selection rules (local field effect) and for the renormalized four-level system (4LS) depicted in Fig. 1 which assumes the formation of biexcitons between excitons with opposite spins. The signal strength is proportional to the strength of the local field in the case of the 2LS and to the renormalization for the 4LS. The peak signal intensities expected for pure local field and pure biexction contributions are summarized in the second and third column of Table 1 for eight experimental configurations applying different linear and circularly polarized pulses. The values are normalized to the signal strength predicted for three parallel linearly polarized pulses. Close inspection of the data reveals remarkable differences of the peak amplitude with polarization geometry for the two coupling models.

Determination of excitonic binding energies in symmetrically strained (GaIn)As/Ga(PAs) multiple quantum wells using quantum beat spectroscopy - Meier, Torsten; Koch, M.; Stolz, W.; Feldmann, J.; Thomas, P.; Göbel, E.O. (Proceedings der 7. International Conference on Superlattices, Microstructures and Microdevices)
We have performed sub-picosecond four-wave mixing experiments on a series of symmetrically strained (GaIn)As/Ga(AsP) multiple quantum wells. We show that these measurements allow a precise determination of exciton binding energies. One of the advantages of this quantum beat method as compared to linear optical methods is that a determination of the exciton binding energy is possible even in the presence of considerable inhomogeneous broadening. In addition, the dependence of the exciton binding energy on the strain in the (GaIn)As quantum well layers suggests that the reduced electron-hole effective mass is not influenced by the increase in strain.

Kreativität und Reproduktion. Annäherung an den Bildungshorizont von Ursula Weida - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs. Forschungsberichte – Projektangebote – Forschungskontexte)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Die Artes liberales im frühen Mittelalter (5.-9. Jh.). Das Quadrivium und der Komputus als Indikatoren für Kontinuität und Erneuerung der exakten Wissenschaften zwischen Antike und Mittelalter - Englisch, Brigitte

On the restricted equivalence for subclasses of propositional logic - Flögel, A.; Kleine Büning, H.; Lettmann, Theodor (RAIRO - Theoretical Informatics and Applications)

Problem Independent Distributed Simulated Annealing and its Applications - Diekmann, Ralf; Simon, Jens (Applied Simulated Annealing)

On Kummer theory and the number of roots of unity in radical extensions of Q - Blömer, Johannes

Parallel Architectures and Their Efficient Use

OCCAM-light: A Language Combining Shared Memory and Message Passing (A First Report) - Kastens, Uwe; Meyer auf der Heide, Friedhelm; Wachsmann, Alf; Wichmann, Friedrich (Proc. 3rd PASA Workshop, PARS Mitteilungen)

Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk

Stanislaw Przybyszewski: Schnee und andere Dramen (Edition) - Eke, Norbert Otto

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 7. Aufzeichnungen. Vermischte Schriften. Text und Kommentar (Edition) - Eke, Norbert Otto; Oellers, Norbert; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Rettung des Sinns. Jaákobs Traum und das Projekt einer Geschichtstheodizee - Eke, Norbert Otto (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

Richard Beer-Hofmann – Zur Einführung - Eke, Norbert Otto; Helmes, Günter (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

„Freiheit ist nur in dem Reich der Träume“. Revolutionsprojektionen deutscher Dramen nach 1789. Ein historischer Aufriß (mit einem Ausblick bis zum Nachmärz) - Eke, Norbert Otto (Grabbe Jahrbuch 12)

Eine Gesamtbibliographie des deutschen Romans 1815-1830. Anmerkungen zum Problemfeld von Bibliographie und Historiographie - Eke, Norbert Otto (Zeitschrift für Germanistik)

„Deutschland ortlos“. Dekonstruktionen des Nationalen bei Heiner Müller - Eke, Norbert Otto (Dichter und ihre Nation)

Integrationsaspekte bei verteilter Software-Entwicklung - Engels, Gregor; Verrijn-Stuart, A.A. (Fortschritt-Berichte VDI)

A Hybrid Query Language for the Extended Entity Relationship Model - Andries, Marc; Engels, Gregor

Towards a Module Concept for Graph Transformation Systems - Ehrig, Hartmut; Engels, Gregor

Abstracts COMPUGRAPH II Workshop - Engels, Gregor; Rozenberg, Grzegorz

Modular, Visual Specifications of Software Processes - Engels, Gregor; Groenewegen, Luuk (Proceedings of the Workshop on Software Process (ISPW 1993), Wadern (Germany))

An Optimal Parallel Dictionary - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Information and Computation)

Strongly adaptive token distribution - Meyer auf der Heide, Friedhelm; Oesterdiekhoff, Brigitte; Wanka, Rolf (Automata, Languages and Programming)

Simple, efficient shared memory simulations - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Proceedings of the fifth annual ACM symposium on Parallel algorithms and architectures - SPAA '93)

Capabilities and complexity of computations with integer division - Lürwer-Brüggemeier, Katharina; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Education in Scientific Visualization - Domik, Gitta (University Education Uses of Visualization in Scientific Computing, Proceedings of the IFIP WG3.2 Working Conference on Visualization in Scientific Computing: Uses in University Education, Irvine, CA, USA, 28-30 July, 1993)

Scientific Visualization - Domik, Gitta (Proceedings of ED Media '93)

An Agenda for Education in Scientific Visualization, Visualization'92 Workshop Report - Domik, Gitta (COMPUTER GRAPHICS-NEW YORK-ASSOCIATION FOR COMPUTING MACHINERY-)

Guidelines for a curriculum in scientific visualization - Domik, Gitta (Computers & Graphics)

Macroscopic and Microscopic Aspects of Glyphs - Domik, Gitta; Joslyn, C; Segura, T (Proceedings of the Vienna Conference on Human Computer Interaction)

Chemisorption of aluminium on GaAs(110) - Schmidt, Wolf Gero; Srivastava, G P (Journal of Physics: Condensed Matter)

Erfahrungen mit einer Multi-Signalprozessorarchitektur (TMS320C40) - Platzner, Marco; Steger, Christian (Mikroelektronik)

Performance Measurements on a Multi-DSP Architecture with TMS320C40 - Platzner, Marco; Steger, Christian; Weiss, Reinhold (Proceedings of the 4th International Conference on Signal Processing Applications & Technology (ICSPAT))

Untersuchung von Schaltnetzteilen mit kontinuierlichen Resonanzschwingungen - Lüdeke, Hans-Peter

́Augen wie Leuchtkäfer ́ - Zur Sprache der Liebe in Mario Vargas Llosas ́ Lob der Stiefmutter - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 37. Mai 1993: Sprachen der Liebe)

Loser und fester Anschluß. Versuch der Neubewertung einer abgelegten Kategorie - Maas, Utz; Tophinke, Doris (Sprachwandel und Sprachgeschichte. FS für Helmut Lüdtke)

Sprachentwicklung in Geschichte und Gegenwart - Maas, Utz; Frankenbusch, Marita; Johannlückens, Ralf; Stöwer-Gaus, Ursula; Striezel, Marion; Tophinke, Doris (Damme. Eine Stadt in ihrer Geschichte)